(untitled) (Research, Society and Development, 2022)
This study aims to describe the experience regarding the use of the Modified Early Obstetric Warning System (MEOWS), in the identification of early maternal deterioration and the activation of the package of interventions (Bundles) in a maternal and child hospital in the State of Pará. A descriptive study, of the experience report type, referring to the period worked as an obstetric nurse in a reference maternity hospital was used as methodology. From the analysis of the reports obtained, the key points of the research were selected, which made it possible to choose the theme that would be worked on, and thus start the theorization of the study. Therefore, articles, books and electronic pages about the subject in question were searched in the databases, in order to increase the understanding of the subject. In the results there is a discussion about the topics: what is MEOWS? How does the service flow in the A&CRO work, using the Obstetric Alert Score and activating bundles? SEPSE Bundle, SHEM Bundle, and SHEG Bundle. Therefore, the study showed that the use of MEOWS associated with the activation of the package of interventions, guarantee immediate assistance to pregnant/puerperal women, promoting a favorable outcome to the identified clinical deterioration.